(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the problem of developing oral activity of students in learning the second language. The authors noted that such obligatory subjects as Russian and English language for bachelor course and professional foreign language for master course occupy a special place in modern higher education. These subjects are aimed to make the educational process not only effective, but also engaging for students and to make them the main characters of this process. The exercises are effective mostly due to the raise of motivation, interest to the subjects, which are an important part of educational process.